Odours in sewer networks nuisance assessment. - Pérez, A. (Water Science and Technology)
As odour nuisance can affect the quality of life, the population is more and more demanding and in many cities sewers are a critical source of odours. Both factors can lead to increasing numbers of complaints due to the odour nuisance perceived by the residents, affecting also the public image of the sewer management companies. Odours associated with sewer networks are very heterogeneous, in as much as the different ?types of odours? encountered are sewer site specific. The state of the art indicates that there are three parameters that play an important role with the nuisance generated by an odour: hedonic odour tone, odour concentration and odour intensity. This paper presents the results of the study on odour nuisance carried out in different points of the sewer network, with the aim to assess the nuisance generated and identify which points of the sewer should be targeted to implement corrective actions. Considering the different parameters assessed, pumping stations have been identified as critical points of odour nuisance in the sewers, being recommended to implement an odour treatment system in order to guarantee the odour comfort of residents.